2019
DOI: 10.2147/jpr.s182876
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of electroacupuncture on nociceptive responses of dorsal horn neurons evoked by noxious colorectal distention in an intensity-dependent manner

Abstract: BackgroundThe transmission of visceral nociception can be inhibited by electroacupuncture (EA) at the spinal level. However, relationships between current intensity and EA-induced analgesia are still lacking. This study compares the effects of different intensities of EA at local acupoints and heterotopic acupoints on nociceptive responses of spinal wide dynamic range (WDR) neurons induced by noxious colorectal distension (CRD).Materials and methodsExperiments were conducted on 40 Sprague Dawley rats anestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…It was demonstrated that noxious and non-noxious stimuli elicited a progressive increase of WDR neurons response along with the increasing of stimulation intensity. The present study demonstrated that the analgesic effect of EA-Ta may be involved in the inhibition of WDR neurons in the spinal dorsal horn, which is consistent with previous reports ( Yu et al, 2019 ; Wang et al, 2020 ; Xue et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…It was demonstrated that noxious and non-noxious stimuli elicited a progressive increase of WDR neurons response along with the increasing of stimulation intensity. The present study demonstrated that the analgesic effect of EA-Ta may be involved in the inhibition of WDR neurons in the spinal dorsal horn, which is consistent with previous reports ( Yu et al, 2019 ; Wang et al, 2020 ; Xue et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, similar to the results of behavioral analyses (Figure 2), 1.0 mg/kg of BVA considerably protected rats from the neuronal hyperexcitation induced by vincristine (Figure 4). Growing evidence implies that the enhanced firing events of WDR neurons represent a state of pain [21,33,34], and therapy-induced decrement of these discharge rates means analgesia [35][36][37][38], indicating that our results could be promising therapeutic options for the clinical management of CIPN.…”
Section: Discussionmentioning
confidence: 84%
“…In a study investigating the relationship between current intensity and EA-induced analgesia in rat with colorectal distension, the effect of EA at ST36 emerged from 0.5 mA, while the effect of EA at PC6 (like ST25, with different segmental innervation with colon) showed no significant difference until 2mA. 25 According to the treatment records, the average current intensity of the two EA groups was 1.5 mA, lower than the current intensity threshold of acupoints with different segmental innervation, which may explain why EA at ST25 did not work and is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%